2016
DOI: 10.1038/srep22384
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Changes of Circulating Long Non-Coding RNAs ZFAS1 and CDR1AS Predict Acute Myocardial Infarction

Abstract: This study sought to evaluate the potential of circulating long non-coding RNAs (lncRNAs) as biomarkers for acute myocardial infarction (AMI). We measured the circulating levels of 15 individual lncRNAs, known to be relevant to cardiovascular disease, using the whole blood samples collected from 103 AMI patients, 149 non-AMI subjects, and 95 healthy volunteers. We found that only two of them, Zinc finger antisense 1 (ZFAS1) and Cdr1 antisense (CDR1AS), showed significant differential expression between AMI pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
73
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(79 citation statements)
references
References 36 publications
5
73
0
1
Order By: Relevance
“…Recently, few literatures have focused on the role of lncRNAs in AMI. For instance, circulating level of lncRNA ZFAS1 in AMI subjects was significantly lower than that in non-AMI subjects, whereas the level of lncRNA CDR1AS in AMI subjects was higher than that in non-AMI subjects [12]. Vausort et al studied expressions of five different lncRNAs in patients with MI, and showed that several lncRNAs were aberrantly expressed in MI patients [13].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, few literatures have focused on the role of lncRNAs in AMI. For instance, circulating level of lncRNA ZFAS1 in AMI subjects was significantly lower than that in non-AMI subjects, whereas the level of lncRNA CDR1AS in AMI subjects was higher than that in non-AMI subjects [12]. Vausort et al studied expressions of five different lncRNAs in patients with MI, and showed that several lncRNAs were aberrantly expressed in MI patients [13].…”
Section: Introductionmentioning
confidence: 99%
“…ZFAS1 (zinc finger antisense 1) is one of cardiac-specific or cardiacrelated lncRNAs. Previous study observed the increased ZFAS1 level in myocardium of AMI mouse models (Zhang et al, 2016a), suggesting the potential involvement of ZFAS1 in AMI. However, its role has not been defined.…”
mentioning
confidence: 78%
“…Serum lncRNA-RP11-445H22.4 has been confirmed as a biomarker for detecting breast cancer and exhibited AUC of 0.904 (Sp = 74%, Se = 92%) [20]. Ying Zhang revealed lncRNA-ZFAS1 and lncRNA-CDR1AS as novel predictors for acute myocardial infarction (AMI) in human whole blood; the AUC was 0.664 or 0.671 when AMI was diagnosed with lncRNA-ZFAS1 or lncRNA-CDR1AS alone and increased to 0.691 when the two lncRNAs were combined [21]. We first evaluated the diagnostic value of lncRNAs in human peripheral blood samples for IS based on lncRNA microarray screening and qRT-PCR validations.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%